Necrotising fasciitis in a patient with monoclonal gammopathy of undetermined significance. Issue 8 (July 2019) - Vella, John X.; Jeavons, Richard P.
To consider the potential risk of an unprovoked infectious disease, such as necrotising fasciitis, being present in patients whereby monoclonal gammopathy of undetermined significance is an active co-morbidity.